Fungal infective endocarditis of polytetrafluoroethylene pulmonary valve with Paecilomyces species following tetralogy of Fallot correction - Anand, Sumeet; Vaidyanathan, Swaminathan; Janeel, Mustafa; Solomon, Neville A. G. (International Surgery Journal, 2020)
Fungal infective endocarditis of the prosthetic pulmonary valve in non immunocompromised host is growing phenomena attributed to the increased use of prosthetic materials. High mortality and neurovascular sequalae is commonly seen in such case if treatment is delayed. Often misdiagnosed as bacterial endocarditis due to closely resembling clinical features and lack of inexpensive and readily available laboratory tests, the diagnosis is often delayed. High index of suspicion and early surgical intervention is needed for early diagnosis and management